التعلم التنظيمي وعلاقته بالرشاقة التنظيمية دراسة حالة شركة الخطوط الجوية الافريقية- بنغازي (Economic studies journal, 2023)
This study aimed at identifying and recognizing the level of the organizational learning and its dimensions (the adaptive learning and the generative learning) and the level of the organizational agility and its dimensions (Sensing, Decision- Making and practice) at the Afriqiyah Airways in the city of Benghazi. The study also aimed at determining the nature and direction of the relationship between the organizational learning and the organizational agility and their dimensions in the company. The study applied the descriptive methodology and in order to achieve its aims. A questionnaire was designed and developed based on some previous studies. The study sample consisted of (220) employees and a random simple sample of (140) employees were selected. The obtained data was analyzed by using the Statistical Program for Social Sciences (SPSS).The findings of the study revealed level an average of learning organizational and organizational agility and their dimensions in the company. Moreover; the study findings showed a strong direct statistically significant relationship between organizational learning and organizational agility and their dimensions. Finally, the study provided a number of recommendations which may contribute in enhancing and reinforcing the role of organizational learning and agility in the Afriqiyah Airways in the city of Benghazi.
Keywords: Organizational Learning; Organizational Agility; Afriqiyah Airways; Benghazi